Is Anorexia Nervosa a Disorder of the Self? A Psychological Approach - Amianto, Federico; Northoff, Georg; Abbate Daga, Giovanni; Fassino, Secondo; Tasca, Giorgio A. (Frontiers in Psychology, 2016)
The debate concerning the pathogenesis and the maintaining factors of eating disorders, anorexia nervosa in particular, is ongoing especially since therapeutic interventions do not result in satisfactory and enduring rates of remission. This paper presents a model for the pathogenesis of eating disorders, based on the hypothesis of a deficiency in the development of the self. We present the theory in light of new evidence concerning the role of attachment insecurity in the development and maintenance of eating disorders. In particular, we define the self in eating disorders in a comprehensive way by taking into account recent evidence from experimental psychology and neurobiology. The paper considers the development of the self in terms of its synchronic (i.e., experienced in the moment) and diachronic (i.e., experienced as continuous over time) aspects. Both synchronic and diachronic aspects of the self are relevant to the expression of eating disorder symptoms. Further, the maturation of the self is interwoven with the development of attachment functioning from infancy to adolescence. This interplay between these developmental processes of the self and of attachment could be crucial in understanding the pathogenesis of eating disorders. The final part of the paper suggests a neurobiological link between the theory of the self in the eating disorders and the spatiotemporal functioning of the brain. Disturbances in spatiotemporal functioning may represent the neurobiological pathway by which deficiencies in the self is related to attachment functions in individuals with eating disorders.